Molecular mechanisms and potential therapeutic targets in the pathogenesis of hypertension in visceral adipose tissue induced by a high-fat diet - Su, Zhenyang; Sun, Jin-Yu; Gao, Min; Sun, Wei; Kong, Xiangqing (Frontiers in Cardiovascular Medicine, 2024)
Background: Hypertension (HTN) presents a significant global public health challenge with diverse causative factors. The accumulation of visceral adipose tissue (VAT) due to a high-fat diet (HFD) is an independent risk factor for HTN. While various studies have explored pathogenic mechanisms, a comprehensive understanding of impact of VAT on blood pressure necessitates bioinformatics analysis. Methods: Datasets GSE214618 and GSE188336 were acquired from the Gene Expression Omnibus and analyzed to identify shared differentially expressed genes between HFD-VAT and HTN-VAT. Gene Ontology enrichment and protein-protein interaction analyses were conducted, leading to the identification of hub genes. We performed molecular validation of hub genes using RT-qPCR, Western-blotting and immunofluorescence staining. Furthermore, immune infiltration analysis using CIBERSORTx was performed. Results: This study indicated that the predominant characteristic of VAT in HTN was related to energy metabolism. The red functional module was enriched in pathways associated with mitochondrial oxidative respiration and ATP metabolism processes. Spp1, Postn, and Gpnmb in VAT were identified as hub genes on the pathogenic mechanism of HTN. Proteins encoded by these hub genes were closely associated with the target organs-specifically, the resistance artery, aorta, and heart tissue. After treatment with empagliflozin, there was a tendency for Spp1, Postn, and Gpnmb to decrease in VAT. Immune infiltration analysis confirmed that inflammation and immune response may not be the main mechanisms by which visceral adiposity contributes to HTN. Conclusions: Our study pinpointed the crucial causative factor of HTN in VAT following HFD. Spp1, Postn, and Gpnmb in VAT acted as hub genes that promote elevated blood pressure and can be targets for HTN treatment. These findings contributed to therapeutic strategies and prognostic markers for HTN.